Evaluation of structural and spectroscopic results of tetragonal tungsten bronze MTa2O6:Eu3+ (M = Sr, Ba, Pb) phosphors and comparison on the basis of Judd-Ofelt parameters - (:unkn) unknown (Elsevier Ltd, 2022)
The crystal structure with different cationic sites and the superiority of allowing doping make TTB (tetragonal tungsten bronze) structures very interesting in terms of exhibiting different physical properties. The new spectroscopic and structural results of MTa2O6:Eu3+ (M = Sr, Ba, Pb) phosphors were presented in the study. The incorporation of europium activator into the different cationic (Sr, Ba, Pb) tunnel structures of TTB crystal with TaO6 octahedral exhibited interesting structural and optical properties. The relationship between coordination number and CTB showed that the highly coordinated A and B sites of TTB crystal caused the CTB to shift to low energy or over 300 nm. The spectral properties of TTB-MTa2O6:Eu3+ (M = Sr, Ba, Pb) phosphors were compared by determining the Judd-Ofelt (JO) intensity parameters from PL emission spectrum. The (decreasing trend of the Ω2 parameter and asymmetry ratio is SrTa2O6:Eu3+>BaTa2O6:Eu3+>PbTa2O6:Eu3+, and the Eu–O bonds of PbTa2O6:Eu3+ compared to other matrices indicated a more ionic character and a relatively high symmetry environment around Eu3+. The deviation of the experimental (βexp) and Judd-Ofelt (βcal) branching ratios for transition 5D0→7F2 are well below 10%, indicating good consistency. All the 5D0 decay profiles of the phosphors are exponential, and slightly reductions occurred in the luminescence lifetimes for SrTa2O6:Eu3+ and BaTa2O6:Eu3+. XRD results of Eu3+ doped SrTa2O6 series of the high-temperature TTB polymorph reported in this study confirmed the single-phase up to 10 mol%. SEM examinations revealed the change of size and shape of SrTa2O6 samples depending on Eu3+ concentration. © 2022 Elsevier B.V.
Keywords: Charge transfer band; Decay time; Judd-Ofelt analysis; TTB